Threat of Human Pathogens in Farmlands: A One Health Perspective - Gaofei Jiang; Xinrun Yang; Thomas Pommier; Yangchun Xu; Qirong Shen; Zhong Wei (Journal of Sustainable Agriculture and Environment)
ABSTRACT A key aspect of “One Health” is to recognize that environmental health and human health are inseparable. In this interconnected network, farmland plays a crucial role, as it serves as a link connecting various ecosystems. However, the threat of human pathogens in farmlands is often overlooked despite growing evidence highlighting its importance as a pressing public health concern via direct and indirect pathways. To address this issue, we advocate the adoption of a “One Health” approach, which relies on strengthening the development of detection tools and emphasizing the importance of sustainable agricultural practices aimed at enhancing soil biodiversity. By doing so, we can effectively disrupt the transmission source and mitigate the risks posed by human pathogens in agricultural ecosystems, ultimately safeguarding both human health and agricultural sustainability.